Cover Image, Volume 39, Issue 9. Issue 9 (31st August 2018) - Wang, Richard T.; Barthelemy, Florian; Martin, Ann S.; Douine, Emilie D.; Eskin, Ascia; Lucas, Ann; Lavigne, Jenifer; Peay, Holly; Khanlou, Negar; Sweeney, Lee; Cantor, Rita M.; Miceli, M. Carrie; et al.
Abstract : On the Front Cover: This cover image, by Richard T. Wang et al., is based on the Research Article DMD genotype correlations from the Duchenne Registry: Endogenous exon skipping is a factor in prolonged ambulation for individuals with a defined mutation subtype, Pages 1193–1202. DOI:10.1002/humu.23561 .